Pembentukan Kelompok Usaha Binaan Anggota Koperasi Credit Union Sumber Sejahtera Banjarmasin - Huda, Isra ul; Lestari, Tina (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Community service aims to establish a Business Group Fostered by Members of the Banjarmasin Sumber Sejahtera Credit Union Cooperative, by conducting socialization and training for vegetable farmer groups in Pinang Habang Village. The implementation of PKM was carried out for 1 (one) day, with the number of participants in the activity as many as 12 people. Participants consisted of supervisors, managers, village pickers, employees, and members of the TP Sejahtera Credit Union Cooperative. Sumber Kasih and vegetable farmer groups. The stages in the activity are preparation, introduction, socialization of MO Empowerment material, conducting training and mentoring to the formation of KUBn. The results of the PkM activities went well and very smoothly, with the socialization can increase the knowledge and understanding of participants about the empowerment operational manual so that they can develop business groups in the future. Training and mentoring activities have formed a member business base group: "Lembayung Merah" complete with the composition of KUBn management who have jointly signed the minutes of KUBn which is also a member of the Sumber Sejahtera credit union cooperative.